KOMUNIKASI INTERPERSONAL DALAM MEMBENTUK KEPERCAYAAN DIRI DI PANTI SOSIAL BINA REMAJA TARUNA JAYA 1 TEBET (STUDI KASUS TERHADAP REMAJA) - Dermawan, Fadly; Haniza, Nurul (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
The problem researchers want to see how interpersonal communication forms the self-confidence of adolescents in the Social Institution. Communication theory used is the theory of social penetration. The research used is a qualitative type with a qualitative descriptive method. The research results were obtained through several data collection techniques, namely observation, interviews, and documentation studies. This study seeks to understand the relationship between adolescent caregivers at the Taruna Jaya 1 Tebet Social Care Center, interpersonal communication barriers in forming trust at the Taruna Jaya 1 Tebet Social Development Institution, and several factors that influence the formation of trust at the Taruna Jaya 1 Tebet Social Institution. This study identified that the relationship between caregivers and adolescents is very closely intertwined, the obstacles found are children who have lying traits, some who are still afraid of meeting new people, and some who often make the same mistakes, and factors that influence the development of self-confidence are educational and environmental factors.